Pengaruh Ransum Basal Dan Feed Additive yang Berbeda Terhadap Bobot, Persentase Karkas Dan Recahan Karkas Ayam Broiler - Helda, Helda; Catootjie, L Nalle; Jehadu, Yohanes (Fakultas Peternakan Universitas Papua, 2021)
The objective of the present study was to evaluate the effect of different basal diet and feed additive on the percentage of carcass and component parts of broilers. This research has been conducted for four months (June to September 2020) at State Polytechnic of Agriculture Kupang. A total of 264 one-day old chicks were distributed to 24 pens (11 birds/pen).The experiment was designed using a 2 x 4 factorial design with 8 tretment combinations and three replications for each treatment. The treatments were control (0% sago) (P0), control (0% sago) + avyzime 0,10 % and phyzyme 0,05% (P1), control (0% sago) + allzime 0,05% (P2), control (0% sago) + synbiotic probio FMplus 40 mL/L drinking water (P3), Diet containing 10% sago (P4), Diet containing 10% sago + allzyme 0,10 % and phyzyme 0,05% (P5), Diet containing 10% sago + allzyme 0,05% (P6) and Diet containing 10% sago + synbiotic probio FMplus 40 mL/L drinking water (P7). The result shows that type of basal diet (TBD) and feed additive (FA) affect (P < 0,05) the carcass weight but it did not afect (P>0,05) carcass percentage of broiler chickens. Except for thigh, TBD did not affect (P>0,05) on component parts of carcass. Feed additive had no effect (P>0,05) on carcass component, with the exception of thigh. Interaction between TBD x FA was significant (P<0,05) only for weight and percentage of carcass and back percentage of broilers. Broilers fed basal diet A plus Allzyme SSF-E had lower weight and percentage of carcass and also back percentage than other treatment diets. To sum up,, 1) basal diet B produced higher carcass weight than basal diet A; 2) supplementation of Allzyme SSF-E on basal diet A reduced the weight and percentage of broiler carcass.